(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2019)
Del Toro’s latest film uses an amphibian creature dragged from the Amazon to reflect on the current situation of immigrants in this country, especially those from south of the border. In the process, the director uses Trump’s nationalist and racist framing of the immigration debate as an opportunity to remake a film he has loved since childhood, "Creature From the Black Lagoon." He places his film in 1962, during the Cuban Missile Crisis, but he insists that he has made a film that, although it takes place in the past, talks about the present. He also reworks a number of the themes and characterizations from his 2006 Spanish-language film "El laberinto del fauno." Both films, one situated in Franco’s Spain shortly after the Civil War, and the other, in J.F.K.’s Camelot, nonetheless present equally chilling visions of systems of political power that foster brutal, authoritarian, and unforgiving social behaviors.